Preparation and characterization of poly lactic acid (PLA) / polyoxymethylene (POM) blends - Muhammad Haniff, Nizulkeman (2016)
Plastics are important material in producing goods, for example electronic casing, plastic bag, diapers, groceries apparatus and automotive parts. Many researches have been conducted that polylactic acid (PLA) was produced as a biodegradable thermoplastic polyester from lactic acid. However, PLA has limited applications due to its inherent brittleness, toughness and low elongation at break. One of the option for improvement is through blending with polyoxymethylene (POM). Melt blending of polylactic acid (PLA) and polyoxymethylene (POM) was performed to investigate the effects of POM loadings on mechanical, morphology and thermal properties of PLA/POM blends. The PLA/POM blends was loaded with 1wt%, 3wt% and 5wt% modified nano clay (C-20).The mechanical properties of the blends were assessed by means of universal testing machine while thermal properties were analysed using differential scanning calorimetry (DSC). Scanning electron microscope was used to study the dispersion and particles size of POM in PLA also C-20 in PLA matrix. The results show, the tensile strength, young’s modulus and elongation at break PLA/POM increased with increasing ratio of clay (C-20). It was found out, the incorporation C-20 is expected increased the tensile strength of the PLA/POM blends.